THE RELATIONSHIP BETWEEN HOSPITAL MANAGEMENT SYSTEM QUALITY AND PATIENT SATISFACTION AT MITRA SEJATI HOSPITAL - Hanry Anta Lesmana; Raskhita Irena Debora Tarigan (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
Background and Purpose. Hospital management systems (HMS) play a critical role in delivering efficient, patient-centered healthcare. In Indonesia, the impact of HMS quality on patient satisfaction remains underexplored. This study aimed to examine the relationship between hospital management system quality and patient satisfaction at Mitra Sejati Hospital in 2025. A quantitative, cross-sectional correlational study was conducted. The study population consisted of patients receiving inpatient or outpatient services at Mitra Sejati Hospital. A purposive sampling technique was used to select 120 participants who met the inclusion criteria: aged ≥18 years, recently treated at the hospital, and capable of completing the questionnaire. Exclusion criteria included patients in critical condition or hospital staff/families. Data were analyzed using Pearson correlation with SPSS v26. Participants’ ages ranged from 19 to 68 years (mean: 41.6), with 40% male and 60% female. Most were outpatient respondents (65%). A significant, moderate positive correlation was found between HMS quality and patient satisfaction (r = 0.602, p < 0.001), indicating that higher HMS quality is associated with greater satisfaction. The study concludes that the quality of hospital management systems significantly influences patient satisfaction. Improving structural and process-related aspects of HMS may enhance service delivery and patient experience. It is recommended that hospitals integrate nurse-responsive systems and regularly evaluate management processes to improve patient outcomes